A comprehensive review on the design and optimization of surface water quality monitoring networks. (October 2020) - Jiang, Jiping; Tang, Sijie; Han, Dawei; Fu, Guangtao; Solomatine, Dimitri; Zheng, Yi
Abstract: The surface water quality monitoring network (WQMN) is crucial for effective water environment management. How to design an optimal monitoring network is an important scientific and engineering problem that presents a special challenge in the smart city era. This comprehensive review provides a timely and systematic overview and analysis on quantitative design approaches. Bibliometric analysis shows the chronological pattern, journal distribution, authorship, citation and country pattern. Administration types of water bodies and design methods are classified. The flexibility characteristics of four types of direct design methods and optimization objectives are systematically summarized, and conclusions are drawn from experiences with WQMN parameters, station locations, and sampling frequency and water quality indicators. This paper concludes by identifying four main future directions that should be pursued by the research community. This review sheds light on how to better design and construct WQMNs. Highlights: Design surface water WQMN is growing and more opportunities in developing countries. Categories, flexibility, optimization objectives of WQMN design methods identified. Design experiences on station location, sampling frequency, water quality indicator. Implications to WQ modelling and smart city, adapt to complex network architectures. Novel design method, coupling new requirement and monitoring tech., better practice.